2015
DOI: 10.1016/j.jagp.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Engage with PST in Late-Life Major Depression: A Preliminary Report

Abstract: Objective The complexity of psychotherapies has been a barrier to community implementation. We used the Research Domain Criteria consensus as a guide to develop Engage, a streamlined, neurobiology-based psychotherapy for late-life depression that may match the skill set of practicing clinicians. This proof of concept study tested the hypotheses that Engage is bioequivalent to Problem Solving Therapy (PST) in reducing depressive symptoms, inducing remission, and ameliorating disability. Methods Engage assumes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 32 publications
0
59
0
Order By: Relevance
“…“Engage”, first described in Alexopoulos and Arean (2014), is a psychological intervention designed to specifically target disturbances in RDoC-defined Positive and Negative Valence Systems through reward exposure , the facilitation of meaningful and rewarding activities. A sample of older adults with MDD received 9 weeks of Engage (Alexopoulos et al, 2015). Symptom improvements within this group were compared to a patient group from a previous study (Alexopoulos et al, 2011), in which participants received problem-solving therapy (PST).…”
Section: Resultsmentioning
confidence: 99%
“…“Engage”, first described in Alexopoulos and Arean (2014), is a psychological intervention designed to specifically target disturbances in RDoC-defined Positive and Negative Valence Systems through reward exposure , the facilitation of meaningful and rewarding activities. A sample of older adults with MDD received 9 weeks of Engage (Alexopoulos et al, 2015). Symptom improvements within this group were compared to a patient group from a previous study (Alexopoulos et al, 2011), in which participants received problem-solving therapy (PST).…”
Section: Resultsmentioning
confidence: 99%
“…Psychotherapies are often too difficult for front line workers to learn and sustain (62) and psychotherapies are rarely used with fidelity in social service settings (26). CM is an intervention that most social service workers are trained to provide.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-nine of these subjects comprised the sample of the proof of concept study reported earlier (13) and 9 were subjects recruited later. They met DSM-IV criteria for major depression.…”
Section: Resultsmentioning
confidence: 99%
“…A proof of concept study comparing Engage with historical comparison group receiving problem solving therapy (PST), showed that Engage is non-inferior to PST in reducing depression in older adults. (13)…”
Section: Introductionmentioning
confidence: 99%